PEMANFAATAN ASAP CAIR DARI SABUT KELAPA MUDA PADA PROSES PENGAWETAN BAKSO JAMUR TIRAM PUTIH DAN IKAN PATIN - Muttakun Muttakun; Akhyar Ali; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Coconut fiber is one of raw materials that can be use to produce liquid smoke. Liquid smoke has been used to extend the shelflife of fish, meat, noodle, soybean curd, and meatballs. Boiling meatballs in a liquid smoke one of the meatballs preserve techniquet. The meatballs that direct boiling within liquid smoke is more effective to extend the shelf life because of active compounf in the liquid smoke will absorbed directly by the meatballs. The white oyster mushroom with catfish meatballs was preserved with young coconut fiber liquid smoke on the research. The research aimed to determine the liquid smoke concentration affect on meatballs preservation. A completely randomized design used with five treatments and three replications, namely: K0 (0% liquid smoke), K1 (1% liquid smoke), K2 (1,5% liquid smoke), K3 (2% liquid smoke), and K4 (2,5% liquid smoke). Data were analyzed statistically with Analysis of Variance and followed by Duncan’s New Multiple Range Test (DNMRT) at 5%. The best treatment was K3 on first day. The meatballs that added with 2% liquid smoke has 5,22 on degree of acid, 8,3×106 microbial total 7,53% protein content and 71,27% water content. Descriptive sensory assesment to K3 (2% liquid smoke) that the choosen treatment were grayish white colour, the aroma of liquid smoke, rather soft texture, not slimy appereance, and overall assesment by panelist rather preferred meatballs. Keywords: liquid smoke, coconut fiber, meatballs, white oyster mushrooms, and catfish